2019
DOI: 10.1186/s12883-019-1395-2
|View full text |Cite
|
Sign up to set email alerts
|

The combined presence of hypertension and vitamin D deficiency increased the probability of the occurrence of small vessel disease in China

Abstract: Background The exact relationship between 25-hydroxyvitamin D [25(OH) D] levels and small vessel disease (SVD) are not clear in China. The aim of this study was to determine such the association between 25(OH) D and SVD in China. Methods We retrospectively enrolled 106 patients with SVD and 115 controls between Jan 2017 and Dec 2017. All the subjects were categorized into three subgroups according to the level of 25 (OH) D: vitamin D deficiency (< 12 ng/ml), insufficien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Otherwise, short-period intraperitoneal injection of 150.000-200.000 IU/kg [44] and 700.000 IU/kg [45] vitamin D with intragastric administration of high-lipid emulsion within approximately 3 months was used to model atherosclerosis in rats. In humans, coexistence of hypertension and vitamin D deficiency enhanced the probability of developing small vessel disease; moreover, patients with this disease were more likely to be male with higher blood pressure and lower 25(OH)D level [46]. Typical hypertensive alterations have not been developed yet during our treatment.…”
Section: Discussion Limitations and Strengthsmentioning
confidence: 94%
“…Otherwise, short-period intraperitoneal injection of 150.000-200.000 IU/kg [44] and 700.000 IU/kg [45] vitamin D with intragastric administration of high-lipid emulsion within approximately 3 months was used to model atherosclerosis in rats. In humans, coexistence of hypertension and vitamin D deficiency enhanced the probability of developing small vessel disease; moreover, patients with this disease were more likely to be male with higher blood pressure and lower 25(OH)D level [46]. Typical hypertensive alterations have not been developed yet during our treatment.…”
Section: Discussion Limitations and Strengthsmentioning
confidence: 94%
“…The authors also found combined presence of hypertension and vitamin D deficiency increased the probability of developing SVD. 24 A cross-sectional study on 57 patients diagnosed with coronary artery disease and 62 age-and sex-matched controls elucidated that low levels of 25 (OH) D are associated with prevalent coronary artery disease independent of cardiovascular risk factors. 25 Previous studies have shown the link between vitamin D deficiency and chronic illnesses like diabetes, hypertension, cardiovascular disease, cancer, immune system diseases, etc.…”
Section: Vitamin D Deficiency and Chronic Illnessesmentioning
confidence: 99%
“…A report showed that insufficient levels of vitamin D increases the risk of stroke ( Zhou R. et al, 2018 ) while some reports showed no effect of low levels vitamin D as a risk factor of stroke ( Perna et al, 2013 ; Skaaby et al, 2014 ). Nonetheless, it has been reported that 78% of patients with ischemic stroke have vitamin D deficiency in China ( Si et al, 2019 ). Due to the inconsistent reports, we aimed to assess the association of vitamin D deficiency with ischemic stroke in a Chinese population (Han race).…”
Section: Introductionmentioning
confidence: 99%